2022
DOI: 10.3171/2022.4.focus2216
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of imposter syndrome among young neurosurgeons and residents in neurosurgery: a multicentric study

Abstract: OBJECTIVE Imposter syndrome (IS) occurs when high-achieving individuals have a pervasive sense of self-doubt combined with fear of being exposed as a fraud, despite objective measures of success. This is one of the main causes of burnout among professionals, threatening their mental health and general well-being. The prevalence and severity of IS among neurosurgery residents and young neurosurgeons has not been yet studied. The primary outcomes of this study were the prevalence and severity of IS. METHODS An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 13 publications
4
32
0
Order By: Relevance
“…Articles examining professional development ranged from resident training to maintenance of certification. 118-151 The most common type of publication in this category was preintervention and postintervention studies. 123,124,128,130,131,136,147,148 The development and implementation of the ACGME milestones was discussed in several articles.…”
Section: Resultsmentioning
confidence: 99%
“…Articles examining professional development ranged from resident training to maintenance of certification. 118-151 The most common type of publication in this category was preintervention and postintervention studies. 123,124,128,130,131,136,147,148 The development and implementation of the ACGME milestones was discussed in several articles.…”
Section: Resultsmentioning
confidence: 99%
“…The mean imposter scores within these studies ranged from 47.0 to 61.2. Frequent‐to‐intense IP was observed in 38.9% of neurosurgeons and neurosurgery residents, with the majority of individuals reporting moderate levels of IP (42.7%) 20 . A significant proportion of radiologists (71%) experienced frequent‐to‐intense IP 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has not consistently demonstrated a clear relationship between job ranks or professional longevity with IP. Among surgeons, IP was more prevalent and worse in trainees and residents than faculty mentors 20,28 . On the contrary, nontenured faculty had lower IP scores than their tenure‐track counterparts 29 and IP was common in those working in top research institutions 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
T he classically quoted refrain of the surgeon, "sometimes wrong, never in doubt," is called into question in the study by Zaed and co-authors, who examine the prevalence of the imposter syndrome (IS) in a cohort of young Italian neurosurgeons and neurosurgical trainees. 1 As the authors note, the imposter phenomenon is characterized by doubt in personal ability and a sense that accomplishments are fraudulent and ill-deserved. Through a survey of neurosurgeons/trainees ≤ 40 years old, the authors examine scores on the Clance Imposter Phenomenon Scale and define scores > 40 (on a range of 6 to 100) to be indicative of IS.
…”
mentioning
confidence: 99%